Predictive performance of fetal aortic isthmus Doppler velocimetry and the cerebro-placental ratio in cases with fetal growth restriction - Elhabashy, Ahmed M.; Aboulenein, Wafaa M.; Abdeldayem, Tamer M.; Elhabashy, Moustafa M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Fetal growth restriction (FGR) is one of the leading causes of intrauterine fetal demise, cerebral palsy and perinatal death. The main cause of FGR is placental insufficiency. Cerebroplacental ratio (CPR) is decreased with the progression of FGR. Fetal aortic isthmus (AoI) Doppler has been suggested as a useful prognostic marker in monitoring of FGR fetuses. Objective of the study is to evaluate the relation between the AoI Doppler and CPR on the perinatal outcome in cases with FGR. Methods: This is a prospective observational cohort study that entailed 100 cases from November 2022 to October 2023. Group A: 50 cases are normal control and group B: 50 cases are FGR. Doppler interrogation of umbilical artery (UA), and middle cerebral artery (MCA), and AoI had been underwent in all cases at GA window: 28-37 weeks within 48 hours before delivery. All cases were assessed after delivery for Apgar score at 10 minutes and admission to the neonatal intensive care unit (NICU). Results: NICU admission was statistically significantly higher in cases and controls with higher AoI pulsatility index (PI) values and lower CPR values. The sensitivity of CPR for prediction of NICU admission was higher than the sensitivity of AoI-PI to predict it (41.94% versus 22.58%). Conclusions: Abnormal fetal AoI Doppler velocimetry is correlated with abnormal CPR in FGR fetuses. Abnormalities in the PI of AoI-PI and CPR in FGR fetuses had association with adverse perinatal outcome. Further studies needed to test the predictive performance of AoI-PI for adverse perinatal outcomes before its enrollment in the daily practice of FGR cases management.